Factor determine employee work life balance at SACC CONVEC Sdn Bhd / Nurain Mohd Zainuddin - Mohd Zainuddin, Nurain (2015)
The issue of work life balance is important to all employees in both sector either public or private sector. The factors of high pressure, long working hours and high personal responsibility leads to negative effect in the employees work life. The pressure of imbalance working life also leads to job dissatisfaction, work stress, create conflict and reduce the family enrichment life. Therefore, these studies are conducted to know the relationship between employee job satisfaction, work stress, family enrichment and workfamily conflict towards the employee work life balance. Responses to a survey of 90 employees from various departments in a private sector company in Shah Alam Selangor were used to test the hypothesis study. A multiple regression was used to predict the factor of job satisfaction, work stress, family enrichment and work-family conflict towards the employee work life balance. Besides, correlation was used to compare the relationship of study variable. The result of multiple regressions reveals that the variable of family enrichment is the factor employee need work life balance. Family enrichment helps the employee to improve their roles as employee and family member. The benefits also include improvement on their ability to multitask on the job and interacting with coworkers. Therefore, it is explain that the family enrichment related to the work life balance.